2018
DOI: 10.4314/sajas.v48i2.16
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome study of linkage disequilibrium in Sahiwal cattle

Abstract: The linkage disequilibrium (LD) is an important tool to study quantitative trait locus (QTL) mapping and genetic selection. In this study, we identified the extent of linkage disequilibrium (LD) in Sahiwal (n = 14) cattle using the bovine high density single-nucleotide polymorphisms (SNPs) BeadChip. After data filtering, 500,968 SNPs comprising 2518.1 Mb of the genome, were used for the LD estimation. The minior allele frequency (MAF) was 0.21 in a substantial proportion of SNPs and mean distance between adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
2
6
1
Order By: Relevance
“…Across the 29 autosomal chromosomes, MAF was highest on chromosome 1 (0.321) and lowest on chromosome 25 (0.309), with an average MAF of 0.317, and showing the lowest (25.5% for LP) and highest SNP proportion (28.8% for QGD) at MAF values of >0.3. These results are comparable with the values reported for different Ethiopian goats [30] and Sahiwal cattle types [31]. However, our study found values higher than the reported MAF values of 0.27 (Drakensberger), 0.26 (Bonsmara), 0.28 (Angus), and 0.28 (Holstein) cattle [32].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Across the 29 autosomal chromosomes, MAF was highest on chromosome 1 (0.321) and lowest on chromosome 25 (0.309), with an average MAF of 0.317, and showing the lowest (25.5% for LP) and highest SNP proportion (28.8% for QGD) at MAF values of >0.3. These results are comparable with the values reported for different Ethiopian goats [30] and Sahiwal cattle types [31]. However, our study found values higher than the reported MAF values of 0.27 (Drakensberger), 0.26 (Bonsmara), 0.28 (Angus), and 0.28 (Holstein) cattle [32].…”
Section: Discussionsupporting
confidence: 90%
“…We estimated the average D’ value at 0.23 across the 29 chromosomes. These results were lower than the previously reported values of 0.48 for various South African commercial goats [37], 0.55 for Sahiwal cattle [31], and the value ranged from 0.12 to 0.52 for Nellore cattle [40], which could be due to the higher power for detecting LD when using markers with many alleles.…”
Section: Discussioncontrasting
confidence: 83%
“…Hence, comparisons were done with foreign breeds. Mustafa et al [46] investigated the Sahiwal dairy breed, which is under threat of extinction, showing an average r 2 value equal to 0.18, which is similar to our Tuscan local breeds (ranged from 0.14 to 0.17). Nevertheless, differences were found for the LD decay, which was significantly more rapid than in Tuscan populations.…”
Section: Discussionsupporting
confidence: 76%
“…It was observed that on an average SNPs located at 50-60 kb distance was having r 2 values at around 0.21 and there was considerable LD decay with increasing distance between SNPs. Mustafa et al (2018) reported that across all the chromosomes the mean LD between SNPs ranged from 0.002 to 0.19 for r 2 with overall mean 0.18 in Sahiwal cattle and a decreasing trend in r 2 was observed as the distance between SNPs increased from 1 kb (0.35) to 100 kb (0.12). Espigolan et al (2013) genotyped Nellore cattle using 444, 986 SNPs and found mean linkage disequilibrium (r 2 ) between adjacent markers as 0.17.…”
Section: Supplementary Tables and Figures Available Onlinementioning
confidence: 99%